Evaluation of Spontaneous and Controlled Fermentation using Different Starter Cultures for Lactic Acid Fermentation of Cilibangi - Shahidah Md. Nor (Universiti Sains Islam Malaysia, 2024)
Fermented chili mash is traditionally prepared by spontaneous fermentation which takes about 1-48 month. This study was conducted to identify and characterize LAB from two sources; autochthonous (isolated from two months pre-fermented chili mash) and allochthonous (isolated from raw milk and home-made yogurt) for their odor characteristics and acceptability using quantitative descriptive analysis (QDA) and hedonic test on fermented chili mash. QDA test revealed that the panellists preferred fermented chili mash that produced intense sourness, sweet, flowery and fruity smell. The chilies were either pre-pasteurized at 80°C for 15 min or non-pasteurized prior to LAB inoculation.Three from six LAB isolates showed desirable odor characteristics and were identified as Lactobacillus plantarum AU2, L.plantarum ALOI and L. pentosus ALO2 using API 50CHL and PCR 16S Rdna methods. These three LABs were further evaluated for their survival, changes in Ph and titratable acidity during 28 days fermentation of fermented chili mash at 35°C. All LABs survived well in both pre-pasteurized and non-pasteurized fermented chili mash (10ᶝ CFU/ml) after 28 days fermentation.Pre-pasteurization of fermented chili mash decreased the mold and yeast count, while inoculation with L.plantarum ALO1 and L.pentosus ALO2 inhibited the growth of mold and yeast. Inoculation of LAB caused significantly rapid reduction in Ph (p˂0.05) and increased in lactic acid content after 7 days fermentation of chili mash as compared to spontaneous fermentation. Qualitatively, volatile organic compound (VOC) is dependent on LAB strains inoculated and ethanol was most abundant compound present in fermented chili mash as detected by static head-space GCMS.In conclusion, inoculation of L. pentosus ALO2 was able to accelerate the fermentation proses and produced acceptable odor characteristics of fermented chili mash as early as 7 days of fermentation.